Anxiety Disorders in Pediatric Dentistry and Their Accordance with Parents' Reports - Esmail Soltani; Najmeh Mohammadi; Ali Sahraian; Lida Vaziri (Shiraz University of Medical Sciences, 2024)
Background: Recent evidence suggests that mental health is associated with dentistry. The aim of the current research was to probe different types of anxiety disorders and phobias in accordance with new changes in the Diagnostic and Statistical Manual of Mental Disorders (DSM5) in pediatric dentistry.Methods: This is a cross-sectional descriptive study. In this research, 282 children aged 7 to 13 years old, and one of their parents who referred to the dental clinic of School of Dentistry of Shiraz completed Youth Anxiety Measure (YAM-I and YAM-II).Results: Result of children and parents' opinions showed a high rate of different types of anxiety (24.4% and 22%) and phobia (27.7% and 27.3%) disorders (P<0.001). Based on children and their parent's reports, there were no significant differences between the girls and boys in different types of anxiety disorders. Also, no significant differences were observed between the two groups in different types of phobias except for the blood type from the child's report and the blood and animal type from the parent's report. Children who had an unpleasant dental experience showed higher anxiety disorders and the results from the parents also confirmed this idea (P<0.001). There was a great deal of agreement between children and their parent's opinions about anxiety disorders (P<0.001).Conclusion: Due to the high rate of anxiety disorders in children, especially in those with unpleasant dental experiences, identification and treatment of these disorders can increase referrals to dentists and consequently improve the oral health.